2003
DOI: 10.1038/sj.mn.7800212
|View full text |Cite
|
Sign up to set email alerts
|

Blood—Brain Barrier Permeability Precedes Senile Plaque Formation in an Alzheimer Disease Model

Abstract: A breakdown of BBB was evident in young 4- to 10-month-old Tg2576 mice. Compromised barrier function could explain the mechanisms of Abeta entry into the brain observed in experimental Alzheimer disease vaccination models. Such structural changes to the BBB caused by elevated Abeta could play a central role in Alzheimer disease development and might define an early point of intervention for designing effective therapy against the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
238
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(248 citation statements)
references
References 26 publications
(41 reference statements)
7
238
0
3
Order By: Relevance
“…However, a growing body of evidence addresses alterations in BBB permeability (typically to large molecules). For example, increases in BBB permeability have been reported to accompany aging (Shah and Mooradian, 1997), Alzheimers dementia (Skoog et al, 1998;Ujiie et al, 2003), type II diabetes (Starr et al, 2003), and hypertension (Mooradian, 1988;Mayhan, 1990;Ueno et al, 2004). BBB permeability also increases with increasing plasma osmolarity (Tamaki et al, 1984), and after the administration of certain drugs (Boertje et al, 1992).…”
Section: Central Nervous Systemmentioning
confidence: 99%
“…However, a growing body of evidence addresses alterations in BBB permeability (typically to large molecules). For example, increases in BBB permeability have been reported to accompany aging (Shah and Mooradian, 1997), Alzheimers dementia (Skoog et al, 1998;Ujiie et al, 2003), type II diabetes (Starr et al, 2003), and hypertension (Mooradian, 1988;Mayhan, 1990;Ueno et al, 2004). BBB permeability also increases with increasing plasma osmolarity (Tamaki et al, 1984), and after the administration of certain drugs (Boertje et al, 1992).…”
Section: Central Nervous Systemmentioning
confidence: 99%
“…In an Alzheimer's disease mouse model, anticipation of an increase in BBB permeability behind the pathogenesis was found. 3 A persistent disruption of the BBB is causally related to progression of neuronal dysfunction, as in temporal lobe epilepsy. 4 These findings indicate that an alteration in the BBB participates in the pathogenesis and progression of neurodegenerative disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Among those factors, elevated levels of circulating LDL cholesterol, independent of APOE genotypes, is strongly linked to the pathogenesis of sporadic AD [6][7][8][9][10]. Of mechanistic importance, we have shown that elevated levels of LDL cholesterol, the essential lipoprotein transporting circulating cholesterol in blood, (1) induces blood-brain barrier (BBB) leakage [7,16] -an early pathological feature of sporadic AD that precedes brain deposition of Aβ [17], (2) disturbs neuronal endolysosome structure and function -another early pathological features of sporadic AD [18], and (3) promotes the development of pathological hallmarks of AD including disrupted synaptic integrity, brain deposition of Aβ, and tau pathology [7]. Furthermore, we have demonstrated in cultured neurons that treatment with LDL cholesterol increased cholesterol accumulation in endolysosomes, disturbed the structure and function of endolysosomes, promoted amyloidogenic processing of AβPP, increased levels of phosphorylated tau, and decreased levels of the presynaptic protein synaptophysin [8].…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that the cholesterol-fed rabbits develop pathological hallmarks of AD including disrupted synaptic integrity, brain deposition of Aβ, and tau pathology [7]. In addition, we have reported that cholesterol-fed rabbits exhibit very early pathological features found in people with AD including increased blood-brain barrier (BBB) leakage [7,16,17] and disturbed neuronal endolysosome structure and function [18]. Furthermore, using primary cultured neurons we demonstrated that LDL cholesterol, the major lipoprotein particle responsible for cholesterol transport in the blood, promoted AβPP internalization, enhanced BACE-1 activity, and increased amyloidogenic processing of AβPP in endolysosomes [8].…”
Section: Introductionmentioning
confidence: 99%